Implementation of the Islamic Leadership Model in Educational Administration at Madrasah Ibtidaiyah - Hamdanah Hamdanah; Mar’atus Sholihah (Faculty of Education and Teacher Training of UINSI Samarinda, 2023)
Madrasah Ibtidaiyah, as an educational institution at the basic level, needs to manage its educational administration to create education that follows the direction of educational goals. Educational administration is necessary to achieve the quality of education; this case must be connected to the role of the madrasah ibtidaiyah principal as a leader in managing the educational administration. Islamic leadership model must be applied so that the implementation of educational administration in madrasah can run as it is supposed to. This study aimed to describe the implementation of the Islamic leadership model as educational administration can increase madrasah ibtidaiyah administration based on Islamic principles, which can establish Islamic education administration well. This research was conducted in descriptive qualitative approaches with research techniques by interviewing school principals and teacher boards to explore the management of Islamic leadership in the madrasah. Observation and documentation were also carried out at Madrasah Ibtidaiyah Al-Ma’arif 02 Jombang, Jember Regency. The results of this study show that the characteristics of the Islamic leadership model in education administration at Madrasah Ibtidaiyah of Al-Ma’arif 02 Jombang-Jember, including justice, amanah, fathonah, tabligh, shiddiq, qona’ah, siasah, and patience. Implementing the Islamic leadership model through educational administration can shape Islamic leadership characters for educators in madrasah ibtidaiyah and harmonize teachers and administrators in school to achieve educational goals.